English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

plz help

2007-04-17 07:57:28 · 3 answers · asked by xxbabeiloveuxx 1 in Science & Mathematics Mathematics

3 answers

2x(x-2)-3=0
is the same as 2x^2-4x-3=0
next use quadratic formula: [4 +-sqrt(16+24)]/4
which equals [4+-sqrt(40)]/4

2007-04-17 08:02:34 · answer #1 · answered by bruinfan 7 · 0 0

Multiply out the left side:
(2x)(x-2) - 3 = 0
2x^2 - 4x - 3 = 0

Now, use the quadratic formula:
x = [(--4) +/- sqrt((-4)^2 - (4*2*-3))] / [2*2]
x = [4 +/- sqrt(40)] / [4]
x = [2 +/- sqrt(10)] / [2]

2007-04-17 15:03:07 · answer #2 · answered by kinuman 2 · 0 0

Quadratic Formula

x = - b ± √b² - 4ac / 2a

2x(x - 2) - 3 = 0

2x² - 4x - 3 = 0

a = 2

b = - 4

c = - 3

x = - (- 4) ± √(- 4)² - 4(2)(- 3) / 2(2)

x = 4 ± √16 - (- 24 / 4

x = 4 ± √16 + 24 / 4

x = 4 ± √40 / 4

x = 4 ± 6.32455532 / 4

- - - - - - -

Solving for +

x = 4 + 6.32455532 / 4

x = 10.32455532 / 4

x = 2.58113883

- - - - - - -

Solving for -

x = 4 - 6.32455532 / 4

x = - 2.32455532 / 4

x = - 0.58113883

- - - - - - -s-

2007-04-17 15:22:20 · answer #3 · answered by SAMUEL D 7 · 0 0

fedest.com, questions and answers